2007
DOI: 10.1007/bf03346353
|View full text |Cite
|
Sign up to set email alerts
|

Looking beyond low bone mineral density: Multiple insufficiency fractures in a woman with post-menopausal osteoporosis on alendronate therapy

Abstract: Insufficiency fractures occur most commonly in the pelvic girdle and in the sacrum, followed by the tibia and the femoral neck. Insufficiency fractures of the femoral diaphyses are rare, with only few reported cases in the literature. The strongest associations exist with untreated osteoporosis. We describe an unusual case of multiple insufficiency fractures in a 73-yr-old Chinese woman who presented with a 10-month history of bilateral groin pain and difficulty with walking in the absence of trauma, diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 80 publications
2
21
0
Order By: Relevance
“…Our study did not find any increasing trend, either in the incidence or hospital discharge rates for any of the subgroups of femoral fractures, in particular shaft or subtrochanteric fractures. Recent case studies raised the question of whether there had been an increase of subtrochanteric or femoral shaft fractures, particularly those with a transverse or short oblique pattern [5,[13][14][15][16]. Although transverse or short oblique type femoral shaft fractures may account for about 50% of all femoral shaft fractures (oblique 37% and spiral 23%) among skeletally mature patients [7], we could not evaluate the number with this specific radiographic pattern in this study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our study did not find any increasing trend, either in the incidence or hospital discharge rates for any of the subgroups of femoral fractures, in particular shaft or subtrochanteric fractures. Recent case studies raised the question of whether there had been an increase of subtrochanteric or femoral shaft fractures, particularly those with a transverse or short oblique pattern [5,[13][14][15][16]. Although transverse or short oblique type femoral shaft fractures may account for about 50% of all femoral shaft fractures (oblique 37% and spiral 23%) among skeletally mature patients [7], we could not evaluate the number with this specific radiographic pattern in this study.…”
Section: Discussionmentioning
confidence: 66%
“…Further information about femur fractures (especially below the hip) is needed at this time to evaluate recent publications of individual case reports and several small case series [1,[13][14][15][16]. These publications have suggested a possible relationship between long-term bisphosphonate use and subtrochanteric or femoral shaft fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Several publications have demonstrated that long-term oral alendronate therapy for osteoporosis is associated with low-energy, insufficiency fractures and that these may be the result of oversuppressed bone turnover. Such insufficiency fractures have become apparent in the clinical setting in a general, uncontrolled population likely with comorbidities and/or receiving concomitant medications, which may be contributory factors [30][31][32][33][34][35][36][37][38][39][40]. Symptoms suggestive of osteonecrosis of the jaw (e.g., localized pain and numbness, exposed bone in the oral cavity, and loose teeth) and atypical fractures with ibandronate were not observed in the DIVA study.…”
Section: Discussionmentioning
confidence: 99%
“…All of the individual case reports of atypical femoral fractures that have been published [12][13][14][15][16][17][18][19][20] illustrate one or more features suggestive of a fracture distinct from the common osteoporosis-related, prosthesis-related, or major traumarelated fracture described above. These include prodromal pain in the thigh or leg for weeks or months prior to the fracture [14,17,18]; use of another antiresorptive or steroid therapy, in addition to the bisphosphonate [12,15,18]; lack of trauma precipitating a fracture [13,14,17,18]; bilaterality (either simultaneous or sequential) [13,15,18,20]; transverse fractures [17]; cortical hypertrophy or thickness [18]; stress reaction on the affected and/or unaffected side [12,14,17,18,20]; poor fracture healing [18,19]; and normal or low bone mass but not osteoporosis in the hip region [11,15,21].…”
Section: Individual Case Reportsmentioning
confidence: 95%
“…These include prodromal pain in the thigh or leg for weeks or months prior to the fracture [14,17,18]; use of another antiresorptive or steroid therapy, in addition to the bisphosphonate [12,15,18]; lack of trauma precipitating a fracture [13,14,17,18]; bilaterality (either simultaneous or sequential) [13,15,18,20]; transverse fractures [17]; cortical hypertrophy or thickness [18]; stress reaction on the affected and/or unaffected side [12,14,17,18,20]; poor fracture healing [18,19]; and normal or low bone mass but not osteoporosis in the hip region [11,15,21]. Several of the case reports describe iliac crest biopsies with very low bone turnover rates; however, this is not a distinguishing feature of patients with atypical fractures on bisphosphonates, as even short-term use of a bisphosphonate results in dramatic reductions in rates of bone turnover [15,22].…”
Section: Individual Case Reportsmentioning
confidence: 99%